The Influence of the Cooperative Integrated Reading and Composition (CIRC) Model with Timeline Media on History Learning Outcomes at Central Tirana High School, Albania - Anila Mullahi (Universitas Negeri Semarang, 2024)
This study aims to determine the influence of the Cooperative Integrated Reading and Composition (CIRC) learning model with Timeline media on students' learning outcomes at Central Tirana High School, as evidenced by increased learning interest in the experimental and control classes. This study uses a quantitative approach with an experimental method and a Quasi-Experimental design, with the design used in this study being a Nonequivalent Control Group Design. Data were taken through learning outcome tests before and after treatment, and quantitative data were obtained from questionnaires and documentation. The sample consisted of XI 5 as the experimental class and XI 7 as the control class. This design made it possible to measure changes in student learning outcomes before and after treatment in both groups. The results showed a significant increase in the experimental class, superior to the control class, from 61.63 to 79.51, while the control class increased from 59.5 to 77.64. The correlation test showed that the r value of 0.612 was more significant than the r table 0.361, so it can be concluded that the CIRC model with Timeline media significantly influences student learning outcomes. Regression analysis produced the equation Ŷ=75.933+0.059(X) with a determination coefficient of 37.45%, showing that this model affects 37.45% of student learning outcomes, the remaining 62.55% is influenced by other factors, one of which is the learning process and the facilities used in the learning process.